Measuring the Strength of State‐Level Alcohol Control Policies. Issue 3 (September 2014) - Erickson, Darin J.; Lenk, Kathleen M.; Toomey, Traci L.; Nelson, Toben F.; Jones‐Webb, Rhonda; Mosher, James F.
<x xml:space="preserve">Abstract</x> We describe a multi‐step method of coding the strength of 18 alcohol policies included in the Alcohol Policy Information System for each of the 50 states. After thoroughly reviewing each policy area, we chose components that were most important in categorizing the strength or restrictiveness of the policy using the following criteria: overall reach, enforceability, and implementation. We determined a unique coding scheme for each policy area. The total number of categories per policy area ranged from two to six, with categories numbered in an ordered sequence from least to most restrictive. We provide three examples of our coding schemes: Keg Registration, Underage Possession, and Sunday Sales. We also rank the states on their alcohol policy sum score. This study demonstrates how alcohol policies can be measured quantitatively, an important step for assessing the effects of alcohol policies on various outcomes.